Triumviri agris dividendis: una leggenda virgiliana (Argos, 2025)
The land confiscations adressed by Virgil’s Eclogues have been widelydiscussed in the bimillennial history of Virgilian studies. In this respect,it has often been argued that a committee of triumviri agris dividendis,consisting of Alfenus Varus, Asinius Pollio, and Cornelius Gallus, wascharged with the distribution of the lands. Different arguments have beenbrought against the historical reliability of this account. In this articleI reexamine the topic from the point of view of the history of Virgilianexegesis. The reconstruction I propose will focus on datable records, inorder to show the evolution of exegesis; later I will focus on non-Servianscholarship, where the different stages of exegesis are more difficult todistinguish.